Effect of adding technologically processed antibodies to interferon-gamma into a parent solution on the structural features of triglycine sulfate crystals grown from this solution - G. O. Stepanov; N. N. Rodionova; R. R. Konstantinov; K. A. Subbotin (Тонкие химические технологии)
Objectives. Ferroelectric triglycine sulfate (TGS) belongs to a group of crystals whose properties are sensitive even to minor changes in growth conditions. The mechanism of spontaneous polarization in TGS is associated with the adjustment of protons which participate in the formation of hydrogen bonds. Therefore, the state of the parent solution plays an important role in the crystal formation. The study aims to investigate the structural features of TGS crystals grown using aqueous alcoholic solutions of technologically processed antibodies to interferon-gamma, in comparison with those of the crystals grown using the control solutions (technologically processed phosphate-buffered saline and intact aqueous alcoholic solution).Methods. X-ray diffraction assay and Raman spectroscopy.Results. The effect of solutions of the technologically processed antibodies to interferongamma added to a parent solution on the growth of TGS single crystals is established. This effect manifests in the changing in occupancy of the proton sublattice of the crystal grown from the parent solution containing technologically processed antibodies to interferon-gamma, as compared with the crystals grown from the control solutions. In the case of the crystal grown from the solution containing technologically processed antibodies to interferon-gamma, this change in the occupancy of the proton lattice is expressed in an increase in the length of N2–C3 bonds.Conclusions. Adding the technologically processed antibodies in the parent solution before the crystal growth can affect the structure of TGS crystals.